2019
DOI: 10.1039/c9nr00391f
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylic acid-capped ruthenium nanoparticles: experimental and theoretical case study with ethanoic acid

Abstract: Joint computational studies and full experimental characterization of NPs is a significant plus in order to apprehend their surface chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 81 publications
(111 reference statements)
8
36
0
Order By: Relevance
“…64 Although it is difficult at that point to safely assign these bands, we can propose the presence of chelate bidentate species. Beside to the bands attributed to carboxylate species, a band at 1940-1960 cm -1 (according to the Ru/ligand ratio) is also observed, as in the work of Poteau et al 49 In our case, however the intensity of this ν CO band is very high, and depends on the Ru/ligand ratio. At a Ru/ligand ratio of 5, two bands are visible at 2040 and 1942 cm -1 ; for a ratio of 10 a single broad band at 1962 cm -1 is observed (Figure 3b), and at a ratio of 20 the band at 1957 cm -1 is very broad with a shoulder at 1800 cm -1 ( Figure S9), which could correspond to bridged CO. 68 The shift of the main band as well as the appearance of new bands could be due to an influence of the CO coverage.…”
Section: Surface Coordination Chemistry Of Carboxylic Ligandssupporting
confidence: 83%
See 4 more Smart Citations
“…64 Although it is difficult at that point to safely assign these bands, we can propose the presence of chelate bidentate species. Beside to the bands attributed to carboxylate species, a band at 1940-1960 cm -1 (according to the Ru/ligand ratio) is also observed, as in the work of Poteau et al 49 In our case, however the intensity of this ν CO band is very high, and depends on the Ru/ligand ratio. At a Ru/ligand ratio of 5, two bands are visible at 2040 and 1942 cm -1 ; for a ratio of 10 a single broad band at 1962 cm -1 is observed (Figure 3b), and at a ratio of 20 the band at 1957 cm -1 is very broad with a shoulder at 1800 cm -1 ( Figure S9), which could correspond to bridged CO. 68 The shift of the main band as well as the appearance of new bands could be due to an influence of the CO coverage.…”
Section: Surface Coordination Chemistry Of Carboxylic Ligandssupporting
confidence: 83%
“…In the case of the use of carboxylic stabilizers for NP synthesis, different coordination modes on metallic surface have been reported: i) monodentate; ii) chelating bidentate; and iii) bridging bidentate. 64 As far as Ru NP stabilized by carboxylate ligands are concerned, Poteau et al reported a bridging bidentate coordination mode (Δν = 145 cm -1 ), 49 in accordance with data reported for molecular (or polymeric)…”
Section: Surface Coordination Chemistry Of Carboxylic Ligandssupporting
confidence: 78%
See 3 more Smart Citations